2008
DOI: 10.1194/jlr.m800130-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic uptake of VLDL in lrpldlrvldlr mice is regulated by LPL activity and involves proteoglycans and SR-BI

Abstract: LPL activity plays an important role in preceding the VLDL remnant clearance via the three major apolipoprotein E (apoE)-recognizing receptors: the LDL receptor (LDLr), LDL receptor-related protein (LRP), and VLDL receptor (VLDLr). The aim of this study was to determine whether LPL activity is also important for VLDL remnant clearance irrespective of these receptors and to determine the mechanisms involved in the hepatic remnant uptake. Administration of an adenovirus expressing LPL (AdLPL) into lrp 2 ldlr 2/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Reductions in plasma cholesterol have also been observed in other mouse models in which LPL expression is increased either directly ( 41-43 ) or indirectly ( 44 ). The cholesterol-lowering effects were observed with increases in LPL that are comparable ( ‫ف‬ 2-to 3-fold) to those associated with inactivation of ANGPTL3 in the present study ( 43 ). Therefore, it is possible that an increase in LPL promotes the clearance of ApoB-containing lipoproteins either by catalyzing changes in lipid content that increase binding of the lipoprotein particles to nonspecifi c binding sites on the cell surface, such as proteoglycans ( 45 ), or by acting as a molecular bridge between lipoproteins and cell surface receptors or proteoglycans ( 46 ), as originally proposed by Felts, Itakura, and Crane ( 47 ).…”
Section: Inactivation Of Angptl3 Does Not Affect Fatty Acid Uptake Bysupporting
confidence: 70%
“…Reductions in plasma cholesterol have also been observed in other mouse models in which LPL expression is increased either directly ( 41-43 ) or indirectly ( 44 ). The cholesterol-lowering effects were observed with increases in LPL that are comparable ( ‫ف‬ 2-to 3-fold) to those associated with inactivation of ANGPTL3 in the present study ( 43 ). Therefore, it is possible that an increase in LPL promotes the clearance of ApoB-containing lipoproteins either by catalyzing changes in lipid content that increase binding of the lipoprotein particles to nonspecifi c binding sites on the cell surface, such as proteoglycans ( 45 ), or by acting as a molecular bridge between lipoproteins and cell surface receptors or proteoglycans ( 46 ), as originally proposed by Felts, Itakura, and Crane ( 47 ).…”
Section: Inactivation Of Angptl3 Does Not Affect Fatty Acid Uptake Bysupporting
confidence: 70%
“…It has also been established by in vitro as well as in vivo studies that SR-BI and its human ortholog Cla-1 can bind apoB-containing lipoproteins and mediate their internalization (3)(4)(5)(6)20 ). This property of SR-BI might depend on the physiological context as hepatic overexpression of SR-BI in hapoB transgenic mice ( 21 ) or attenuated expression in LDLR knockout ( 22 ) mice did not affect the LDL catabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have shown that exchangeable apolipoproteins, especially ApoE and ApoC3, participate in the assembly and secretion of VLDL, the precise roles of the apolipoproteins are largely unknown [74]. heparan sulfate proteoglycan (HSPG), interacting with or without lipoprotein receptors, including LDLR and SR-B1 [75]. The interaction between exchangeable apolipoproteins and lipoproteins confers stability and hydrophilicity through exchange with other high-affinity apolipoproteins [65].…”
Section: Hcv Usurps Lipid Metabolism and Lipoprotein Circulationmentioning
confidence: 99%